The Sox2: GFP+/− knock‐in mouse model does not faithfully recapitulate Sox2 expression in skin. Issue 11 (25th August 2017) - Salz, Lucia; Driskell, Ryan R.
Abstract: Hair follicle heterogeneity may be regulated by distinct dermal papillae (DP) that represent mesenchymal lineages, which can be defined by Sox2 expression. However, it was recently shown that GFP expression in the Sox2: GFP+/− mouse model occurs in the DPs of all hair follicle types, challenging the idea that hair follicle heterogeneity can be defined by DP heterogeneity. Here, we investigated whether the knock‐in mouse model faithfully expresses GFP when compared to endogenous Sox2 expression. The results reveal that GFP expression is aberrant in both the infundibulum of hair follicles and in the DPs. Consequently, we provide an explanation for the aberrant expression of the knock‐in gene based on the original cloning strategy for the mouse model in the context of a newly identified regulatory element associated within the coding region of Sox2.